Results from 2011 for the transportMYpatient program for overcoming transport costs among women seeking treatment for obstetric fistula in Tanzania. Issue 3 (22nd December 2012) - Fiander, Alison; Ndahani, Clement; Mmuya, Kaspar; Vanneste, Tom
Abstract: Background: The Comprehensive Community Based Rehabilitation in Tanzania (CCBRT) Disability Hospital program transport MY patient was launched in 2009 to address transport costs, which are a major barrier to patients accessing CCBRT health services. The initiative uses mobile phone technology to transfer funds to cover transport costs. Methods: Data were reviewed for fistula patients using the transport MY patient scheme in 2011, noting region of referral. Average costs of using the scheme were calculated and the location of "ambassadors" by region was recorded. Results: Between 2005 and 2009, CCBRT repaired approximately 170 fistulas annually, increasing to 286 in 2010 and 339 in 2011. In 2011, the transport MY patient initiative transported 166 fistula patients from almost all regions in Tanzania, accounting for 49% of total repairs. Conclusion: The increase in referrals to CCBRT during 2011 as a result of the transport MY patient program shows that transport costs are a real barrier to accessing care. Analysis of geographic referral data informs outreach and community sensitization initiatives, concentrating on regions of low referral. The use of mobile phone technology to transfer funds represents an innovative means of overcoming a major barrier to healthcare access for patients in low‐income countries.